Cell Death Pathways Associated with Photodynamic Therapy: An Update. (16th January 2018) - Kessel, David; Oleinick, Nancy L.
Abstract: Photodynamic therapy (PDT) has the potential to make a significant impact on cancer treatment. PDT can sensitize malignant tissues to light, leading to a highly selective effect if an appropriate light dose can be delivered. Variations in light distribution and drug delivery, along with impaired efficacy in hypoxic regions, can reduce the overall tumor response. There is also evidence that malignant cells surviving PDT may become more aggressive than the initial tumor population. Promotion of more effective direct tumor eradication is therefore an important goal. While a list of properties for the "ideal" photosensitizing agent often includes formulation, pharmacologic and photophysical elements, we propose that subcellular targeting is also an important consideration. Perspectives relating to optimizing PDT efficacy are offered here. These relate to death pathways initiated by photodamage to particular subcellular organelles. Abstract : Phase‐contrast and fluorescence microscopy (nuclear labeling) of A549 non–small‐cell lung cancer cells illustrating properties of PDT‐induced apoptosis, necrosis and paraptosis.